Exotisme, initiatives marchandes et pratiques alimentaires dans les commerces grecs de Bruxelles - Katerina Seraïdari (Cahiers Balkaniques)
Based on ethnographical data collected since 2009, this article analyzes the representations, the commercial activities and the food practices of Greek migrants in Brussels. Greeks have contributed to develop and to re-orient the food choices and the taste of their clientele, to whom they propose products that seemed exotic before progressively becoming part of the local gastronomy. Through its opposition to this tendency to banalization, the new generation tries to reinvent Greek cuisine and to replace Greek products that became transcultural by other elements, less known and less industrialized.